What interventions improve outcomes for patients with isolated low levels of high‐density lipoprotein cholesterol (HDL‐C)?. Issue 12 (December 2015) - Haver, Amy; Irwin, Manasa; Haugh, Amy; Wilson, Stephen A.
Abstract : Evidence‐Based Answer : Niacin, fibrates, and cholesteryl ester transfer protein (CETP) inhibitors may raise HDL, but do not improve cardiovascular outcomes compared with an active comparator (such as a statin). However, niacin and fibrates decrease nonfatal myocardial infarctions (MIs) compared with placebo (SOR: A, meta‐analysis). Exercise alone, diet alone, and a combination of exercise and diet do not increase HDL (SOR: C, metaanalysis with disease‐oriented outcomes).